The The Utilization of Social Media as an Information Platform for Hajj by the Ministry of Religious Affairs (A Descriptive Analysis of the Instagram Account @informasihaji) - Aida Fathonah; Abdul Rozaq; Mustofa Hilmi (Dinasti International Journal of Education Management And Social Science, 2024)
The increasing number of prospective Hajj and Umrah pilgrims each year impacts the information management system that must be communicated to the pilgrims. Effective and efficient dissemination of information is crucial in the organization of Hajj and Umrah, serving as a preventive measure against misinformation and requiring various information to be socialized to the public. This study analyzed the utilization of the social media platform Instagram as an information medium for Hajj by the Ministry of Religious Affairs through the account @informasihaji. We employed a descriptive qualitative method. The data collection techniques used documentation of information and posts on the @informasihaji Instagram account, encompassing images, videos, and captions. For the data analysis,the Miles and Huberman theory was used. The findings indicate that the @informasihaji account has successfully provided timely and easily understandable information through a variety of visual posts and collaborations with other accounts. However, some shortcomings remain, such as an unorganized feed layout and a lack of two-way interaction with followers. In the context of Media Richness Theory, this account reflects aspects like quick feedback and variety in cues, but there is still room for improvement in forming a more personal connection with its followers.